Determining the time course of CYP3A inhibition by potent reversible and irreversible CYP3A inhibitors using a limited sampling strategy - Katzenmaier, Stephanie Katharina; Markert, Christoph; Riedel, Klaus-Dieter; Burhenne, Jürgen; Haefeli, Walter E.; Mikus, Gerd (Clinical pharmacology & therapeutics, 2011)
We established a new limited sampling strategy to assess CYP3A activity and evaluated the time course of reversible (voriconazole) and irreversible (ritonavir) CYP3A inhibition. In this randomized trial, two groups, each with eight healthy participants, received CYP3A inhibitors voriconazole or ritonavir orally for 9 days, with 3 mg midazolam (MDZ) administered before the inhibitor treatment, on days 1, 2, 3, 5, 8, and 9 during inhibitor treatment, and on days 10, 11, and 12 (3 days) after discontinuation. Plasma MDZ area under the curve (AUC) between 2 and 4 h after oral administration in the form of a solution strongly correlated with MDZ clearance. Using this parameter, maximum inhibition of voriconazole and ritonavir was calculated to have occurred only 48 h after starting of the inhibitor (percentage of baseline MDZ clearance, voriconazole: 10.6%; ritonavir: 8.4%). Recovery of CYP3A activity occurred with a half-life of 24 h after voriconazole, whereas ritonavir inhibition was still strong 3 days after discontinuation. These findings underscore the substantial and gradual alterations in dose requirements in the first days of and after such combination therapies.